RegulatingFreedom of Opinion, Expression, and Media Work in International Conventions - Gogh, Prof. Dr. Marouf Omar Kul; Bakr, Drifan Abdel Qader (Journal of Legal and Political Studies, 2019)
The study examines the most important international and regional conventions regulating the freedom of opinion and expression and the media work, based on the descriptive method, by expaining the most important items and materials related to this subject and then analyzing it, and then we tried to search for the response of internal laws in the Kurdistan Region of Iraq to these general international and regional conventions.
Keywords: international convention; national convention; materials; items